Parent wellbeing, family screen time and socioeconomic status during early childhood predict physical activity of aboriginal and Torres Strait islander children at ages 8–13 - Macniven, Rona; Stanley, Rebecca M; Biles, Brett; Dumuid, Dot; Olds, Tim; Okely, Anthony D; Chandler, Paul; Evans, John (My University, 2022)
Objective Physical activity is holistically linked to culture and wellbeing among Aboriginal and Torres Strait Islander peoples, the First Nation Peoples of Australia. Socioecological correlates of high physical activity among Indigenous children include living in a remote area and low screen time but little is known about early life determinants of physical activity. This paper examines sociodemographic, family, community, cultural, parent social and emotional wellbeing (SEWB) determinants of physical activity among Aboriginal and Torres Strait Islander children. Design Longitudinal cohort study. Method The Longitudinal Study of Indigenous Children, the largest First Nations child cohort study in the world, primarily collects data through parental report. Multiple logistic regression analyses examined Wave 1 (age 0–5 years) predictors of achieving ≥1 h/day of physical activity at Wave 9 (aged 8–13 years). Results Of the 1181 children, 596 (50.5 %) achieved ≥1 h of physical activity every day. Achieving ≥1 h/day of physical activity at Wave 9 was associated with the following Wave 1 determinants: high parent SEWB (Resilience; Adjusted Odds Ratio (OR) 1.87 (95 % CI: 1.32–2.65), living in remote (OR 3.66 (2.42–5.54)), regional (OR 2.98 (2.13–4.18) or low socioeconomic areas (OR 1.85 (1.08–3.17), main source of family income not wages/salaries (OR 0.66 (0.46–0.97)), and if families played electronic games (OR 0.72 (0.55–0.94)). Conclusions To achieve high physical activity levels among Aboriginal and Torres Strait Islander children, high parental culture specific SEWB and low family screen time in early life may compensate for apparently low socio-economic circumstances, including living in remote areas.
Journal of Science and Medicine in Sport
Keywords: Childhood and child development; Health and wellbeing; Lifestyle